Macro-Financial Linkages in the High-Frequency Domain: The Effects of Uncertainty on Realized Volatility - Guglielmo Maria Caporale; Menelaos Karanasos; Stavroula Yfanti (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper estimates a bivariate HEAVY system including daily and intra-daily volatility equations and its macro-augmented asymmetric power extension. It focuses on economic factors that exacerbate stock market volatility and represent major threats to financial stability. In particular, it extends the HEAVY framework with powers, leverage, and macro effects that improve its forecasting accuracy significantly. Higher uncertainty is found to increase the leverage and macro effects from credit and commodity markets on stock market realized volatility. Specifically, Economic Policy Uncertainty is shown to be one of the main drivers of US and UK financial volatility alongside global credit and commodity factors.
Keywords: C22; C58; D80; E44; G01; G15; 330; asymmetries; economic policy uncertainty; HEAVY model; high-frequency data; macro-financial linkages; power transformations; realized variance; risk management